Artificial Intelligence (AI) di Mata Tenaga Kesehatan di Sulawesi Utara - Leksono, Daniel; Kornarius, Yoke Pribadi; Caroline, Angela; Gusti, Triningtyas Elisabeth Putri; Gunawan, Agus (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
The development of health service technology in the current era is swift. This development is both an opportunity and a threat to health technology in Indonesia. Artificial Intelligence is an exciting thing in this era (Digital Health Era) because it displays and provides convenience in digitalization. This research article aims to determine the attitudes of health workers regarding their intentions towards using AI in the world of work and to describe the attitudes of health workers towards AI. The health workers who were the sample for this study were health workers at hospitals in North Sulawesi. The method used in this research is quantitative description and qualitative with interviews. Cross-sectional data collection was done using questionnaires and interviews. This research shows that attitude (behavior/GAAIS) has a 53% influences intention to use (Intention to Use) AI. Health workers expressed quite positive views about the existence of AI, having high hopes that it could be used to make daily work easier. However, an important thing concerns them: AI cannot replace health workers regarding patient service because it does not have the human side, such as empathy, feelings, and direct service (touch). This research is expected to complement the literature on the development of AI technology, improve and enrich readers regarding AI and the world of health, and make the world of health and health workers more advanced and better, especially in digitalizing health